Α-Solanine induces ferroptosis in nasopharyngeal carcinoma via targeting HSP90α/p53 axis. (May 2023) - Cui, Xuehui; Gong, Yitong; Ge, Jun; Feng, Xiaofei; Xiong, Xuemei; Shi, Zhen; Zheng, Qiusheng; Li, Defang; Bi, Sixue
Graphical abstract: Highlights: α-Solanine can induce ferroptosis in NPC HK-1and 5-8F cells. HSP90α was the direct target of α-solanine action in NPC HK-1 and 5-8F cells. HSP90α/p53 axis was highly involved in α-solanine-mediated ferroptosis. α-Solanine-mediated tumor suppression in vivo was associated with ferroptosis. Abstract: α-Solanine, a natural small molecule compound, mainly derived from potato tubers with anti-tumor and anti-inflammatory effects. No studies have yet confirmed that α-solanine can act on tumor cells via ferroptosis, and its molecular mechanism is unclear. The present study aimed to study whether α-solanine could induce nasopharyngeal carcinoma (NPC) cell death through ferroptosis and its specific molecular mechanism. Here, α-solanine was proven to trigger ferroptosis in NPC cells via targeting HSP90α directly. The primary manifestations of α-solanine-induced ferroptosis in NPC HK-1 and 5-8F cells were increased levels of ROS, MDA, iron and altered mitochondrial structure. Moreover, there was a noticeable decrease in SLC7A11 and GPX4 expression. Mechanistic study showed that α-solanine directly binds to HSP90α which promotes p53 expression and ultimately inhibits the level of SLC7A11 to inactivate GPX4. Collectively, our study revealed the potential application of α-solanine in the treatment of nasopharyngeal carcinoma through ferroptosis.